Education, Political Discontent, and Emigration Intentions: Evidence from a Natural Experiment in Turkey - Z. Eylem Gevrek; Pinar Kunt; Heinrich Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2019)
We exploit the 1997 school reform that increased compulsory schooling from 5 to 8 years to investigate the causal effect of education on emigration intentions. Our IV estimates indicate that an additional year of schooling increases the probability of reporting the intention to emigrate by 24 percentage points. Moreover, we provide evidence that the identified effect of education on emigration intentions does not operate through financial dissatisfaction but rather through displeasure at a bleak political environment that better educated people are more keenly aware of.
Keywords: I21; I25; I31; 330; education; migration; political discontent